Influence of Body Composition Parameters on Anaerobic Strength of Lower Extremities in Female Football Players - Ana Lilić; Marko Joksimovic; Stefania D'Angelo; Siniša Karišik; Shamal Hamad; Novica Gardašević (OVS LLC, 2020)
The aim of this study was to investigate the influence of body composition on the anaerobic strength of the lower extremities, as well as the prediction of body composition on the results of anaerobic ability in professional football players. Materials and Method. The sample of respondents consists of female football players who compete in the highest rank of the competition, the Serbian Super League. The total number of respondents included in the study was 21 female football players (age 19.38 ± 3.69, body height 166.48 ± 6.17 cm, body weight 59.98 ± 7.09 kg). The study is of a transversal nature and testing was done in the pre-competition period. The sample of measuring instruments used in the research are body composition and assessment of anaerobic strength of the lower extremities. Assessment of body composition was performed indoors using a multifrequency bioelectric impedance (Inbody 770). Variables for estimating the anaerobic strength of the lower extremities were obtained using a bicycle ergometer (Monark 839E) in the Wingate Anaerobic Test. Results. The results of body composition show a statistically significant influence on the prediction of maximum anaerobic strength of the lower extremities in professional female football players (p < 0.05), as well as on the overall work in the anaerobic zone and the mean values ​​of anaerobic strength. Regression analysis of the influence of body composition on the parameters of maximum strength in (W/kg) and fatigue rate does not show statistically significant results. Conclusion. There is a statistically significant influence of body composition, such as: body weight, lean body mass (%), muscle mass in absolute and relative values, on the values ​​of maximum anaerobic strength, mean values ​​of anaerobic strength and overall work in professional female footballers.